PERAN TEKNOLOGI DALAM MENINGKATKAN TANGGAP DARURAT TERHADAP KEGAWATDARURATAN MATERNAL: TINJAUAN LITERATUR DAN IMPLEMENTASI - Sholihah, Aisyah Imro'Atus; Yusri Dwi Lestari (Jurnal Medicare, 2025)
Maternal emergencies remain a leading cause of high maternal mortality in developing countries, including Indonesia. This study employs a systematic literature review and case studies of technology implementations in maternal emergency settings, covering mobile applications, early warning systems, and telemedicine. The review finds that technology adoption can accelerate clinical decision-making, strengthen coordination among healthcare providers, and enhance service access for pregnant women in remote areas. Nonetheless, infrastructure limitations, inadequate training of medical personnel, and system integration issues persist as major barriers. In conclusion, optimizing the role of technology in maternal emergency response requires a collaborative approach among policymakers, healthcare providers, and technology developers.